Alkali-activated gelling material and preparation method and application thereof

By adding industrial solid waste, recycled aggregate and electronic waste to alkali-excited gelling materials, combined with polymer emulsion and retarder, the problems of environmental pollution caused by electronic waste landfill and poor mechanical properties of alkali-excited concrete are solved, and alkali-excited gelling materials with high strength, low volume weight and crack resistance are achieved.

CN119735385APending Publication Date: 2025-04-01SHENZHEN WENKE LANDSCAPE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411872225.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize electronic waste, resulting in landfill and environmental pollution. The alkali-activated concrete has poor mechanical properties and is prone to cracking after simply filling the electronic waste.

Method used

An alkali-excited gelling material is adopted, which includes alkali-exciting agents, industrial solid waste, natural aggregates, recycled aggregates, electronic waste, polymer emulsions and retarders. Through specific proportions and preparation methods, the compressive strength and cracking resistance of the material are improved.

Benefits of technology

The high strength, low volume weight and good crack resistance of alkali-activated gelling materials are achieved, and the heavy metals in electronic waste are utilized to avoid secondary pollution, which has significant environmental protection and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735385A_ABST
    Figure CN119735385A_ABST
Patent Text Reader

Abstract

The invention discloses an alkali-activated cementitious material and a preparation method and application thereof, and relates to the technical field of building materials. The alkali-activated cementitious material comprises the following raw materials: an alkali activator, industrial solid waste, natural aggregate, recycled aggregate, electronic waste, a polymer emulsion and a retarder. The application recycles electronic waste, which can not only reduce the bulk density of alkali-activated concrete, increase the compressive strength of alkali-activated recycled aggregate concrete, and enhance the anti-cracking performance of alkali-activated concrete; in addition, the strong anti-permeability of alkali activation can be used to fix heavy metal materials in electronic waste in the alkali-activated cementitious material, thereby avoiding secondary pollution of heavy metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an alkali-activated gelling material and a preparation method and application thereof. Background Art

[0002] In recent years, the growth rate of electronic waste is almost three times that of global urban waste. Electronic waste has complex components, a wide range of sources, and many types. It often contains harmful metals. Direct landfill can easily cause environmental pollution and endanger human physical and mental health. Electronic waste mainly includes flame retardants, plastics, PVC and other harmful substances. When incinerated, it will pollute the air, which brings great difficulties to the recycling of electronic waste.

[0003] Alkali-activated material is a very promising green cementitious material. Alkali-activated cementitious material is usually composed of alkali activator and activating material. It originated from cementitious materials in the middle of the last century. In 1957, Ukrainian scholar Glukhovsky used slag as raw material to prepare a composite cementitious material with good shrinkage resistance. The composite cementitious material has the advantages of high strength, short gelling time period and strong anti-permeability. Compared with silicate cement, when the compressive strength of concrete is the same, the splitting tensile strength of alkali-activated slag concrete is basically close to that of silicate cement concrete, but its bending strength is higher than that of silicate cement concrete. Therefore, if discarded electronic waste can be recycled and reused, the preparation of alkali-activated materials is undoubtedly an economical and environmentally friendly project. However, since electronic waste is simply filled into concrete, the prepared concrete has poor mechanical properties and is prone to cracking. Summary of the invention

[0004] The main purpose of the present invention is to propose an alkali-activated gelling material and its preparation method and application, aiming to improve the utilization rate of industrial solid waste and electronic waste, and to prepare an alkali-activated gelling material with high strength, strong crack resistance and good promotion and application value.

[0005] To achieve the above object, the present invention provides an alkali-activated gelling material, which comprises the following raw materials: an alkali activator, industrial solid waste, natural aggregate, recycled aggregate, electronic waste, polymer emulsion and retarder;

[0006] In one embodiment, the alkali-activated gelling material comprises the following raw materials, measured in parts by mass:

[0007] 10-30 parts of alkali activator;

[0008] 20-40 parts of industrial solid waste;

[0009] 3.5 to 13 parts of electronic waste;

[0010] 4-6 parts of polymer emulsion;

[0011] 10-20 parts of natural aggregate;

[0012] 10-20 parts of recycled aggregate; and

[0013] Retarder 0.1 to 0.5 parts.

[0014] In one embodiment, the alkali activator includes at least one of water glass, sodium hydroxide and sodium carbonate; and / or, the industrial solid waste includes at least one of slag powder, fly ash, silica fume and steel slag; and / or, the electronic waste includes at least one of PVC, high impact polystyrene, ABS plastic, PC plastic and polyimide; and / or, the polymer emulsion is water-based polyurethane; and / or, the natural aggregate includes natural limestone, granite or igneous rock; and / or, the recycled aggregate includes construction waste blocks or construction waste aggregates; and / or, the retarder is barium chloride.

[0015] In one embodiment, the electronic waste includes electronic plastic powder and electronic plastic fiber, wherein the mass ratio of the electronic plastic powder to the electronic plastic fiber is (1-20):1.

[0016] In one embodiment, the preparation step of the electronic plastic powder includes: crushing and sorting the electronic waste to obtain the electronic plastic powder, wherein the size of the electronic plastic powder is 0.5-6 mm, and the density of the electronic plastic powder is 1-2 g / cm 3 .

[0017] In one embodiment, the preparation step of the electronic plastic fiber includes: melting and spinning electronic waste to obtain the electronic plastic fiber, and the size of the electronic plastic fiber is 0.5 to 3 cm.

[0018] The present invention also provides a method for preparing the alkali-activated gelling material as described above, comprising the following steps:

[0019] S1. mixing industrial solid waste, electronic waste, natural aggregate, recycled aggregate and retarder to obtain a first mixture;

[0020] S2, adding a base activator to the first mixture to obtain a second mixture;

[0021] S3, adding polymer emulsion to the second mixture to obtain a third mixture;

[0022] S4, placing the third mixture into a mold for curing to obtain an alkali-activated gelling material.

[0023] In one embodiment, in step S4, the curing temperature is 15-25° C.; and / or the curing relative humidity is 85-95%.

[0024] The present invention also includes the use of the alkali-activated gelling material as described in any one of the above or the alkali-activated gelling material prepared by the method for preparing the alkali-activated gelling material as described in any one of the above in the industrial field.

[0025] In the technical solution provided by the present invention, industrial solid waste, recycled aggregate and electronic waste are added to the alkali-activated cementitious material, which can reduce the bulk density of the alkali-activated concrete, increase the compressive strength of the alkali-activated cementitious material, and enhance the anti-cracking performance of the alkali-activated concrete; in addition, the strong anti-permeability of alkali activation can be used to fix the heavy metal materials in the electronic waste in the alkali-activated cementitious material, thereby avoiding secondary pollution of heavy metals. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work. Figure 1 This is a test diagram of the compressive strength of the alkali-activated gelling material prepared by adding different amounts of alkaline activators to the emulsion according to the embodiment of the present invention; Figure 2 This is a durability test diagram of different polymer-to-rubber ratios provided in the present invention. The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0026] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.

[0027] Alkali-activated material is a very promising green cementitious material. Alkali-activated cementitious material is usually composed of alkali activator and activating material. It originated from cementitious material in the middle of the last century. In 1957, Ukrainian scholar Glukhovsky used slag as raw material to prepare a composite cementitious material with good anti-shrinkage performance. The composite cementitious material has the advantages of high strength, short gelling time period and strong anti-permeability. Compared with silicate cement, when the compressive strength of concrete is the same, the splitting tensile strength of alkali-activated slag concrete is basically close to that of silicate cement concrete, but its flexural strength is higher than that of silicate cement concrete. Therefore, if discarded electronic waste and industrial solid waste can be recycled and reused, the preparation of alkali-activated materials is undoubtedly an economical and environmentally friendly project.

[0028] In view of this, the present invention provides an alkali-activated gelling material, comprising an alkali activator, an activating material, a natural aggregate, a recycled aggregate, electronic waste, a polymer emulsion and a retarder.

[0029] In the technical solution provided by the present invention, industrial solid waste, recycled aggregate and electronic waste are added to the alkali-activated cementitious material, which can reduce the bulk density of the alkali-activated concrete, increase the compressive strength of the alkali-activated cementitious material, and enhance the anti-cracking performance of the alkali-activated concrete; in addition, the strong anti-permeability of alkali activation can be used to fix the heavy metal materials in the electronic waste in the alkali-activated cementitious material, thereby avoiding secondary pollution of heavy metals.

[0030] It should be noted that the composition of electronic waste is complex, including flame retardants, plastics, heavy metals and other substances.

[0031] Furthermore, the alkali-activated cementitious material comprises the following raw materials, measured by weight: 10 to 30 parts of alkali activator; 20 to 40 parts of industrial solid waste; 3.5 to 13 parts of electronic waste; 4 to 6 parts of polymer emulsion; 10 to 20 parts of natural aggregate; 10 to 20 parts of recycled aggregate; and 0.1 to 0.5 parts of retarder.

[0032] It should be noted that alkali activators accelerate the activity of waste through chemical reactions and promote the formation of cementitious materials. Industrial solid waste and recyclable waste are both environmentally friendly and can increase material strength. Polymer emulsions can enhance the toughness, durability and crack resistance of materials. Electronic waste and natural aggregates and recycled aggregates are used to provide supporting structures. Retarder delays the setting time. This combination can effectively utilize industrial waste and electronic waste, reduce environmental pollution, and provide excellent mechanical properties. Controlling these components within the above-mentioned proportion range can not only control the maximum performance of the material, but also optimize the mechanical properties of the alkali-activated cementitious material.

[0033] Furthermore, the alkaline activator includes at least one of water glass, sodium hydroxide and sodium carbonate; the alkaline activator has good activity and can fully activate the potential gelling properties in the waste. Water glass, sodium hydroxide or sodium carbonate can be used as the alkaline activator, or two of them can be selected, which can be adjusted according to actual needs.

[0034] The industrial solid waste includes at least one of slag powder, fly ash, silica fume and steel slag. Since slag powder, fly ash, silica fume and steel slag are common industrial wastes, easy to obtain and rich in active substances, the selection of different components in industrial solid waste enhances the adaptability and diversity of the material, so that the cementitious material can show good stability and performance under various environmental conditions.

[0035] The electronic waste includes plastic, and the plastic includes at least one of PVC, high-impact polystyrene (HIPS), ABS plastic, PC plastic and polyimide. The recycling of electronic waste reduces the processing cost of plastic waste and has a significant environmental protection effect. The plastic in the electronic waste has high strength and light density, which can effectively reduce the bulk density of alkali-activated concrete and increase the strength of concrete.

[0036] The natural aggregate includes common aggregates such as natural limestone, granite or igneous rock, and the particle size ranges from 5 to 15 cm.

[0037] The recycled aggregate is construction waste aggregate, including bricks, cement blocks, concrete blocks, etc. from demolished buildings, all of which have a wide range of sources.

[0038] The retarder is barium chloride, which can effectively adjust the setting time.

[0039] Adding alkali-activated gelling material to electronic waste after sorting can further improve the utilization rate and performance of alkali-activated gelling material, so the electronic waste is prepared into electronic plastic powder and electronic plastic fiber respectively. In some embodiments of the present invention, the electronic waste includes electronic plastic powder and electronic plastic fiber, and the mass ratio of the electronic plastic powder to the electronic plastic fiber is (1-20):1. Specifically, the mass ratio of the electronic plastic powder to the electronic plastic fiber can be 1:1, 2:1, 10:1, 15:1, 20:1, etc. Within the above range, the electronic plastic powder can reduce the density of the alkali-activated material and increase its compressive strength. The electronic plastic fiber can provide additional structural support and improve the stress distribution inside the alkali-activated material. By adjusting the ratio of the electronic plastic powder and the electronic plastic fiber, the physical properties of the alkali-activated gelling material, such as density, crack resistance and compressive strength, can be improved, thereby enhancing its application value.

[0040] In some embodiments of the present invention, the preparation step of the electronic plastic powder includes: crushing and sorting the electronic waste to obtain the electronic plastic powder, wherein the average particle size of the electronic plastic powder is 0.5-6 mm, and the density of the electronic plastic powder is 1-2 g / cm 3 When the electronic plastic powder is large, since the contact surface between plastic and concrete is a weak area, too large plastic will cause the bonding strength of concrete to decrease, and too small particles will result in higher processing costs.

[0041] Specifically, the steps of preparing the electronic plastic powder include:

[0042] Dismantle the electronic waste, recycle the electronic garbage, crush and screen the electronic garbage to obtain electronic plastic powder, until the average particle size of the electronic plastic powder is 0.5-6mm and the density of the electronic plastic powder is 1-2g / cm 3 , those that do not meet the size can be crushed continuously.

[0043] In some embodiments of the present invention, the preparation steps of the electronic plastic fiber include: melting and spinning electronic waste to obtain electronic plastic fibers, the size of the electronic plastic fibers is 0.5 to 3 cm, and electronic plastic fibers of this size can form good structural support in alkali-activated gelling materials, significantly improving the material's tensile resistance and crack resistance.

[0044] Specifically, the steps of preparing the electronic plastic fiber include:

[0045] The electronic waste is recycled into plastics, and the plastics are sorted, crushed, cleaned, dried, extruded, melted, spun, wound and cut into a series of operation steps to obtain electronic plastic fibers with a size of 0.5 to 3 cm.

[0046] The present invention also provides a method for preparing the alkali-activated gelling material as described above, comprising the following steps:

[0047] S1. mixing industrial solid waste, electronic waste, aggregate and retarder to obtain a first mixture;

[0048] S2, adding a base activator to the first mixture to obtain a second mixture;

[0049] S3, adding polymer emulsion to the second mixture to obtain a third mixture;

[0050] S3, placing the third mixture into a mold for curing to obtain an alkali-activated gelling material.

[0051] In the preparation steps of the present invention, solid waste, electronic waste and other dry materials are first mixed, then the alkali activator is added, and finally the liquid of the polymer emulsion is added and mixed, and a three-step mixing method is adopted to ensure the uniform distribution and good reaction of each component, thereby improving the comprehensive performance of the material. In addition, the step-by-step mixing method can prevent the polymer emulsion and the alkali activator from reacting prematurely when they are not evenly mixed, thereby improving the operability of the construction.

[0052] It should be noted that adding an alkali activator to the first mixture to obtain a second mixture, and adding a polymer emulsion at a suitable speed to obtain a third mixture can ensure mixing uniformity, guarantee the alkali activation effect and the enhancement effect of the polymer emulsion, avoid local overheating or incomplete reaction, and improve the consistency and stability of the alkali-activated gelling material.

[0053] In one embodiment, in step S4, the curing temperature is 15-25°C; and / or the curing relative humidity is 85-95%. Preferably, the curing is carried out at a temperature of 20°C and a relative humidity of 90%. When the material is cured under appropriate temperature and humidity conditions, sufficient hydration reaction can be achieved to ensure that its mechanical strength and durability meet the design requirements and avoid cracking and deformation problems.

[0054] The present invention also includes the use of the alkali-activated cementitious material as described in any one of the above items or the alkali-activated cementitious material prepared by the preparation method of the alkali-activated cementitious material as described in any one of the above items in the industrial field, specifically, it can be used in non-load-bearing building components, emergency repair projects, road paving and the like.

[0055] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0056] The experimental materials are as follows:

[0057] The modulus of water glass is 2.0;

[0058] The slag powder is S95 grade slag powder produced by Qingdao Zhongkuang Hongyuan, with a specific surface area of ​​410m 2 / kg;

[0059] Steel slag is a solid waste discharged by a steel enterprise, and its components include CaO, SiO2, FeO and other oxides;

[0060] The fly ash is Class I fly ash, provided by Qingdao Municipal Engineering Group Concrete Engineering Co., Ltd.;

[0061] Steel slag, slag and fly ash have different contents of each component, but contain the same types of multiple substances, as shown in Table 1 below.

[0062] Table 1 Comparison of chemical composition of steel slag, mineral powder and fly ash

[0063] Material CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> cement 60-65 20-25 4-8 2-5 Steel slag 35-55 8-25 1-5 3-9 slag 30-50 25-45 7-20 / Fly ash 2-7 35-60 15-40 5-25 Material CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> cement 60-65 20-25 4-8 2-5

[0064] The natural aggregate is limestone with a particle size of 5-15cm and an apparent density of 2750kg / m 3 ;

[0065] The recycled aggregate is mainly construction waste blocks purchased from Chengtou Construction Waste Disposal Co., Ltd., with a void ratio of 54.6% and a bulk density of 1220kg / m 3 , apparent density 2520kg / m 3 , crushing index is 22%, firmness (mass loss) is 12%, chloride ion content is 0.002%, sulfide grade sulfate content (by SO3 mass) is 0.5%, water absorption is 2.52%, mud content is 2.38%;

[0066] The water-based polyurethane was produced by Shenzhen Jitian Chemical and had a solid content of 45%;

[0067] The electronic plastic powder and electronic plastic fiber in electronic waste come from Shenzhen Liqi Recycling Resources Co., Ltd.

[0068] Example 1

[0069] Provided is an alkali-activated gelling material, comprising the following raw materials in parts by mass: 15 parts of water glass, 30 parts of steel slag, 4.5 parts of electronic plastic powder, 0.5 parts of electronic plastic fiber, 4.5 parts of waterborne polyurethane, 15 parts of natural aggregate, 15 parts of recycled aggregate and 0.3 parts of barium chloride, wherein each part is 1g.

[0070] The preparation step of the alkali-activated gelling material comprises: weighing the above-mentioned mass of steel slag, electronic plastic powder, electronic plastic fiber, natural aggregate, recycled aggregate and barium chloride and mixing them to obtain a first mixture;

[0071] The first mixture was stirred in a stirrer for 30 seconds, and then liquid water glass was slowly added, and stirring was stopped after 1 minute to obtain a second mixture;

[0072] Adding waterborne polyurethane to the second mixture and stirring for 2 minutes to obtain a third mixture;

[0073] The third mixture is taken out and put into a mold, and vibrated to form a 40 mm×40 mm×160 mm cubic specimen. The specimen is cured at a temperature of 20° C. and a relative humidity of 90% to an appropriate age and then tested.

[0074] Example 2

[0075] Provided is an alkali-activated gelling material, which is the same except that the masses of the components of the alkali-activated gelling material are different. The alkali-activated gelling material comprises the following raw materials in parts by mass: 15 parts of water glass, 30 parts of fly ash, 4.5 parts of electronic plastic powder, 0.5 parts of electronic plastic fiber, 4.5 parts of waterborne polyurethane, 15 parts of natural aggregate, 15 parts of recycled aggregate and 0.3 parts of barium chloride, wherein each part is 1g.

[0076] Example 3

[0077] Provided is an alkali-activated gelling material, which is the same except that the masses of the components of the alkali-activated gelling material are different. The alkali-activated gelling material comprises the following raw materials in parts by mass: 15 parts of water glass, 30 parts of slag, 4.5 parts of electronic plastic powder, 0.5 parts of electronic plastic fiber, 4.5 parts of waterborne polyurethane, 15 parts of natural aggregate, 15 parts of recycled aggregate and 0.3 parts of barium chloride, wherein each part is 1g.

[0078] Example 4

[0079] Provided is an alkali-activated gelling material, which is the same except that the masses of the components of the alkali-activated gelling material are different. The alkali-activated gelling material comprises the following raw materials in parts by mass: 15 parts of water glass, 10 parts of steel slag, 10 parts of fly ash, 20 parts of slag, 4.5 parts of electronic plastic powder, 0.5 parts of electronic plastic fiber, 4.5 parts of waterborne polyurethane, 15 parts of natural aggregate, 15 parts of recycled aggregate and 0.3 parts of barium chloride, wherein each part is 1g.

[0080] Example 5

[0081] Provided is an alkali-activated gelling material, which is the same except that the masses of the components of the alkali-activated gelling material are different. The alkali-activated gelling material comprises the following raw materials in parts by mass: 15 parts of water glass, 10 parts of steel slag, 10 parts of fly ash, 20 parts of slag, 3 parts of electronic plastic powder, 3 parts of electronic plastic fiber, 4.5 parts of waterborne polyurethane, 15 parts of natural aggregate, 15 parts of recycled aggregate and 0.3 parts of barium chloride, wherein each part is 1g.

[0082] Example 6

[0083] Provided is an alkali-activated gelling material, which is the same except that the masses of the components of the alkali-activated gelling material are different. The alkali-activated gelling material comprises the following raw materials in parts by mass: 15 parts of water glass, 10 parts of steel slag, 10 parts of fly ash, 20 parts of slag, 10 parts of electronic plastic powder, 0.5 parts of electronic plastic fiber, 4.5 parts of waterborne polyurethane, 15 parts of natural aggregate, 15 parts of recycled aggregate and 0.3 parts of barium chloride, wherein each part is 1g.

[0084] Example 7

[0085] Provided is an alkali-activated gelling material, which is the same except that the masses of the components of the alkali-activated gelling material are different. The alkali-activated gelling material comprises the following raw materials in parts by mass: 15 parts of water glass, 10 parts of steel slag, 10 parts of fly ash, 20 parts of slag, 4.5 parts of electronic plastic powder, 0.5 parts of electronic plastic fiber, 1 part of waterborne polyurethane, 15 parts of natural aggregate, 15 parts of recycled aggregate and 0.3 parts of barium chloride, wherein each part is 1g.

[0086] The mass fractions of some raw materials of the alkali-activated gelling materials provided in Examples 1 to 7 are shown in Table 2.

[0087] Table 2: Partial mass fractions of raw materials in Examples 1 to 9

[0088]

[0089] Comparative Example 1

[0090] Provided is an alkali-activated gelling material, wherein the other raw materials and mass fractions are the same as those in Example 1 except that no electronic waste is added to the activated material.

[0091] Comparative Example 2

[0092] Provided is an alkali-activated gelling material, wherein no industrial solid waste is added to the activated material, and other raw materials and mass fractions are the same as those in Example 1.

[0093] Comparative Example 3

[0094] Provided is an alkali-activated gelling material, wherein the other raw materials and mass fractions are the same as those in Example 1 except that no polymer emulsion is added to the activated material.

[0095] Performance Testing

[0096] 1) Determination of the amount of emulsion and water glass

[0097] The amount of emulsion (polymer emulsion) and alkaline activator (water glass) was changed to 20%, 30%, 40% and 50%, and the rest was the same as in Example 1. The compressive strength test of the prepared alkali-activated gelling material was performed. The test results are as follows: Figure 1 As shown in the figure, as the emulsion content decreases, the compressive strength of alkali-activated concrete decreases. In fact, as the emulsion content increases, the compressive strength of alkali-activated concrete decreases first and then increases. When it reaches a certain amount, it shows a downward trend. The best content is 30% of the water glass content. Therefore, other performance tests will be continued with this content.

[0098] 2) The bulk density, number of cracks, and compressive strength at 7d and 28d of the alkali-activated cementitious materials prepared in the above Examples 1 to 7 and Comparative Examples 1 and 2 were selected respectively, and the average value of three identical samples was taken to record the results.

[0099] The test method is as follows:

[0100] Compressive strength: The compressive strength is tested according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0101] Bulk density: GB / T50080-2002 "Standard for test method of concrete density".

[0102] The test results are shown in Table 3.

[0103] Table 3 Test results of Examples 1 to 7 and Comparative Examples 1 to 3

[0104]

[0105]

[0106] From Table 3, we can see that:

[0107] By comparing Examples 1, 2, and 3, it can be concluded that slag powder has the highest activity, fly ash is second, and steel slag has the lowest activity.

[0108] By comparing Examples 4, 5, and 6, it can be concluded that as the content of electronic plastic powder increases, the compressive strength of the alkali-activated concrete increases slightly, and the bulk density of the concrete decreases.

[0109] By comparing Examples 4 and 5, it can be concluded that with the addition of electronic plastic fibers, the number of cracks in alkali-activated concrete is significantly reduced and the crack resistance is significantly improved.

[0110] Comparing Examples 1 to 7 with Comparative Examples 1 and 2, it can be concluded that without adding electronic waste, since plastic particles can be used as lightweight aggregates and plastic fibers can improve the stress distribution inside the material, the strength of the comparative example is reduced and it is easy to crack after the plastic particles and plastic fibers are lost.

[0111] Since no industrial solid waste is added to Comparative Example 2, and since industrial solid waste contains a large amount of amorphous silicon and aluminum compounds with potential gelling activity, not adding industrial solid waste makes the gelling property of the alkali-activated material worse, Comparative Example 2 has many cracks and poor mechanical properties.

[0112] The durability test was performed on Example 7 and Comparative Example 3, and the test method was as follows:

[0113] Using RCM method (rapid chloride ion migration coefficient method):

[0114] The external electric field is used to make the chloride ions outside the specimen migrate to the inside of the specimen. After a period of time, the specimen is split, and silver nitrate solution is sprayed on the newly split section. The depth of chloride ion penetration is measured based on the generated white silver chloride precipitation, and the chloride ion diffusion coefficient of concrete is calculated.

[0115] The calculation formula of the chloride ion diffusion coefficient tested by the RCM method is:

[0116]

[0117] Among them, D RCM is the chloride ion diffusion coefficient determined by the RCM method (m2 / s), T is the average value of the initial and final temperatures of the anolyte (K), h is the specimen height (m), xd is the chloride ion diffusion depth (m), t is the power-on test time (s), and a is a coefficient related to temperature and time.

[0118] Test results such as Figure 1 As shown in Table 4

[0119] Table 4

[0120] project <![CDATA[Chloride ion migration coefficient (10 -12 m 2 / s)]]> Comparative Example 3 9 Example 7 4 Example 8 4

[0121] Depend on Figure 2 From Table 4, we can see that: Figure 2The polymer-binder ratio of the horizontal axis refers to the mass ratio of the waterborne polyurethane and the corresponding binder (steel slag, fly ash, slag powder). As the polymer-binder ratio increases, the chloride ion migration coefficient shows a downward trend. This means that when the polymer content is relatively higher, the blocking ability of the embodiment to chloride ions is stronger, and since no polymer emulsion is added to Comparative Example 3, the chloride ion migration coefficient of Comparative Example 3 is much higher than that of the embodiment, because the addition of polymer emulsion is conducive to reducing the migration of chloride ions and improving durability.

[0122] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. An alkali-activated gelling material, characterized in that: The alkali-activated gelling material comprises the following raw materials: an alkali activator, industrial solid waste, natural aggregate, recycled aggregate, electronic waste, polymer emulsion and a retarder.

2. The alkali-activated gelling material according to claim 1, characterized in that: The alkali-activated gelling material comprises the following raw materials in parts by mass: 10-30 parts of alkali activator; 20-40 parts of industrial solid waste; 3.5 to 13 parts of electronic waste; 4-6 parts of polymer emulsion; 10-20 parts of natural aggregate; 10-20 parts of recycled aggregate; and Retarder 0.1-0.5 parts.

3. The alkali-activated gelling material according to claim 1, characterized in that: The alkaline activator comprises at least one of water glass, sodium hydroxide and sodium carbonate; and / or, The industrial solid waste includes at least one of slag powder, fly ash, silica fume and steel slag; and / or, The electronic waste includes at least one of PVC, high-impact polystyrene, ABS plastic, PC plastic, polyimide, etc.; and / or, The polymer emulsion is waterborne polyurethane; and / or, The natural aggregate comprises natural limestone, granite or igneous rock; and / or, The recycled aggregate includes construction waste blocks or construction waste aggregate; and / or, The retarder is barium chloride.

4. The alkali-activated gelling material according to claim 3, characterized in that: The electronic waste includes electronic plastic powder and electronic plastic fiber, wherein the mass ratio of the electronic plastic powder to the electronic plastic fiber is (1-20):

1.

5. The alkali-activated gelling material according to claim 4, characterized in that: The preparation steps of the electronic plastic powder include: crushing and sorting the electronic waste to obtain the electronic plastic powder, wherein the size of the electronic plastic powder is 0.5-6 mm, and the density of the electronic plastic powder is 1-2 g / cm 3 .

6. The alkali-activated gelling material according to claim 4, characterized in that: The preparation steps of the electronic plastic fiber include: melting and spinning electronic waste to obtain the electronic plastic fiber, and the size of the electronic plastic fiber is 0.5-3 cm.

7. A method for preparing an alkali-activated gelling material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. mixing industrial solid waste, electronic waste, natural aggregate, recycled aggregate and retarder to obtain a first mixture; S2, adding a base activator to the first mixture to obtain a second mixture; S3, adding polymer emulsion to the second mixture to obtain a third mixture; S3, placing the third mixture into a mold for curing to obtain an alkali-activated gelling material.

8. The method for preparing an alkali-activated gelling material according to claim 7, characterized in that: In step S3, the curing temperature is 15-25° C.; and / or, The relative humidity of the curing is 85-95%.

9. Use of the alkali-activated gelling material according to any one of claims 1 to 6 or the alkali-activated gelling material prepared by the method for preparing the alkali-activated gelling material according to any one of claims 7 or 8 in industrial fields.